On the possible reason for superconductivity strengthening in multiwall carbon nanotubes: High-Temperature Superconductivity - Gaididei, Yu.B.; Loktev, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Basing on the structural peculiarity of two-layer graphene which consists of translational and energetical nonequivalency of carbon atoms from different sublattices, it is shown that the density of long-wave electronic states at the Fermi level is finite (in contrast to the monolayergraphene). It is suggested that the same may be the reason why the critical temperature of superconducting transition in multiwall nanotubes more than ten times higher than in single-wallnanotubes.